Handheld optical coherence tomography for clinical assessment of dental plaque and gingiva - Won, Jungeun (J Biomed Opt, 2020)
Significance: Optical coherence tomography (OCT) offers high spatial resolution and contrast for imaging intraoral structures, yet few studies have investigated its clinical feasibility for dental plaque and gingiva imaging in vivo. Furthermore, the accessibility is often limited to anterior teeth due to bulky imaging systems and probes. Aim: A custom-designed, handheld probe-based, spectral-domain OCT system with an interchangeable attachment was developed to assess dental plaque and gingival health in a clinical setting. Approach: Healthy volunteers and subjects with gingivitis and sufficient plaque were recruited. The handheld OCT system was operated by trained dental hygienists to acquire images of dental plaque and gingiva at various locations and after one-week use of oral hygiene products. Results: The handheld OCT can access premolars, first molars, and lingual sides of teeth to visualize the plaque distribution. OCT intensity-based texture analysis revealed lower intensity from selected sites in subjects with gingivitis. The distribution of the dental plaque after one-week use of the oral hygiene products was compared, showing the capability of OCT as a longitudinal tracking tool. Conclusions: OCT has a strong potential to display and assess dental plaque and gingiva in a clinical setting. Meanwhile, technological challenges remain to perform systematic longitudinal tracking and comparative analyses.